Trends in the 30-day minimum winter runoff of rivers flowing out of lake Sevan - Margaryan, Varduhi; Reshetchenko , Svitlana; Vardanyan , Vahram; Frunzikyan, Hovakim (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Formulation of the problem. Studies of trends in the minimum 30-day winter runoff of rivers flowing out of the lake. Sevan has acquired great practical importance and significant interest from the point of view of calculating the ecological flow, due to the increased use of water resources for various types of economic activities, in particular, in connection with the development of the economy, hydropower, irrigation, population growth and improving living standards. Calculations of the minimum runoff are especially relevant in relation to solving the problems of water supply to settlements, industrial and agricultural enterprises, as well as assessment of irrigation norms of agricultural plots. The aim of the work. Analysis and assessment of trends in the minimum 30-day winter runoff of rivers flowing out of the lake Sevan. Methods. The following methods were used in the work: mathematical-statistical, correlation, cartographic, extrapolation, interpolation, spatial analysis, analogy. Results. During the research, the characteristics of the winter minimum 30-day water consumption for the entire observation period were calculated for hydrological posts on the rivers of the lake Sevan basin, which have a number of observations for 40 years or more. Supply curves are constructed, the values of the winter minimum 30-day runoff are estimated, with security of 90, 95 and 99.5% for 12 sites. The values of the flow rates, its coefficients of variation (Cv) and asymmetry (Cs) are determined. The analysis of the temporal distribution of the studied hydrological characteristics was carried out, the coefficients of the linear trend of the minimum 30-day winter runoff were determined. Close correlations have been obtained between the values of the average monthly minimum water consumption and the minimum 30-day winter water consumption. These dependencies can be used to predict the minimum 30-day winter water consumption of the rivers of the territory under consideration. It is established that for the rivers of the lake Sevan basin is characterized by synchronicity of fluctuations in annual and winter runoff. It was revealed that most of the rivers flowing into the lake Sevan (by more than 58% of posts), there is an increase in the amount of winter runoff, i.e. a positive trend in its change. Based on the results obtained, a distribution map of the linear trend coefficients of the minimum 30-day winter runoff in m3/sec / 10 years with an observation period from december to march was constructed.